Towards an African theological ethic of earth care: Encountering the Tonga lwiindi of Simaamba of Zambia in the face of the ecological crisis - Kaoma, Kapya (HTS teologiese studies, 2017)
The mounting ecological catastrophe and its negative effects on humanity and future generations of life, demand proactive actions. The ongoing crises of deforestation, air and water pollution, land degradation and many other ecological predicaments are critical global moral and justice issues. Although postcolonial Africa’s economic theories undermine the integrity of Creation, Africans are equally responsible. Following Pope Francis’ invitation to Creation care, I argue that the lwiindi [the annual rain-calling ceremony] illustrates ecological concerns and possesses ecological insights that can aid, inform and positively transform Africa’s ecological actions. The article opens with a brief discussion on the growing ecological consciousness in global Christianity and Africa. It employs the lwiindi to illustrate the ecological role of ancestors as guardians of the land. It is from this perspective that the Enlightenment influenced concept of ‘progress’, is examined. The article concludes with some critical reflections on the environment and Tonga culture.